A User-Printable Three-Rate Rain Gauge Calibration System - Lopez Alcala, Jose M.; Udell, Chester J.; Selker, John S. (Frontiers in Earth Science, 2019)
Our objective was to develop and validate a freely downloadable, open-source, 3D printed rain gauge calibrator that can be adjusted for a wide range of gauges. The calibrator applies constant low, medium, and high-intensity water delivery rate, and allows the user to modify the design to conform to their system based on parametric design. The design may be modified and printed using freely available computer-aided design (CAD) software. Currently available devices for calibration tend to be designed for specific rain gauges, are expensive, employ low-precision water reservoirs, are not field portable, and do not offer the flexibility needed to test the ever more popular small-aperture rain gauges (smaller surface area to catch precipitation than the classical 200mm standard). To overcome the fact that different 3D printers yield different print qualities, we devised a simple post-printing step that controls critical dimensions to assure robust performance. Specifically, orifices of the calibrator are drilled to reach the target flow rates. Laboratory tests showed that flow rates of 25, 50, and 83 ml/min were consistent between prints (coefficient of variation of 3.9, 2.2, and 1.8, % respectively), and between trials of each part, while the total applied water was precisely controlled (0.1%) by the use of a volumetric flask as the reservoir. The entire system costs under US$10.